PENERAPAN PEMBELAJARAN MENDALAM SILA SILA PANCASILA UNTUK MENILAI 8 PROFIL LULUSAN DIMENSI BERIMAN DAB BERTAKWA KEPADA TUHAN YANG MAHA ESA DI KELAS ENAM MI TARBIYATUL AKHLAQ - Abdul Matin, Anas; Zuni Eka Tiyas Rifayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of deep learning on the Pancasila principles in the sixth grade of MI Tarbiyatul Akhlaq and to assess the achievement of the eight graduate profiles in the dimension of Faith and Devotion to God Almighty. The background of this research arises from the limited application of Pancasila values, which are often only memorized without being deeply internalized in students’ daily behavior. Through a deep learning approach, the learning process focuses on strengthening understanding of meaning, conceptual interconnection, and the application of divine values in real life. This study employs a descriptive qualitative method with data collection techniques including observation, observation sheets, and documentation of sixth-grade students at MI Tarbiyatul Akhlaq. The results indicate that the implementation of deep learning improves students’ character in five aspects of morality: religious morality, personal morality, morality towards others, morality towards nature, and morality towards the nation. Teachers act as facilitators guiding students to connect divine values with real actions such as discipline in worship, responsibility, respect, environmental awareness, and patriotism. This learning model enables students not only to understand the Pancasila principles cognitively but also to internalize their values in daily life. Therefore, the deep learning model is effective in assessing and cultivating the eight graduate profiles of Pancasila, especially in the spiritual and moral dimensions within Islamic elementary education (Madrasah Ibtidaiyah).